The Religious Court in Indonesia: A Preliminary Overview of Mahkamah Syar’iyah Aceh - Hasnul Arifin Melayu (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
An Act to regulate the Religious Court (PA) as one of the judicial institutions in Indonesia experienced changes in its history. One of the factors that influenced these changes was political and social circumstances that occurred in both government and society. This paper discusses the social and political influences on the existence of religious courts in Indonesia.